Europejskie źródła konstytucyjnego federalizmu północnoamerykańskiego - Balicki, Ryszard; Ławniczak, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the European models that have helped to shape the North American political system, including constitutional achievements of the first European republics of San Marino, Switzerland, and the Netherlands. The authors argue that the US Constitution was created as a result of the synthesis of the English legal and political tradition and continental political theory, developed by Locke, Rousseau and Montesquieu.
Keywords: źródła prawne; Konstytucja USA; republikańska tradycja Europy